2007
DOI: 10.1007/s00464-005-0700-x
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of upper gastrointestinal studies versus clinical signs for gastrointestinal leaks after laparoscopic gastric bypass

Abstract: According to our data, UGI studies are the most predictive of an early leak diagnosis. Clinical signs alone may not be as useful in predicting leaks early after laparoscopic gastric bypasses. Routine early postoperative UGI studies are a reasonable approach to predicting leaks after LRYGB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
30
1
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(35 citation statements)
references
References 25 publications
2
30
1
2
Order By: Relevance
“…These 2 studies found clinical signs to be less sensitive and there fore support the use of routine contrast studies. 35,36 Some of the common reasons quoted in support of rou tine Gastrografin swallows on POD 1 are documentation (especially for young surgeons), ability to detect strictures, and the consideration that many CT scanners are not bar iatric patient-rated.…”
Section: Discussionmentioning
confidence: 99%
“…These 2 studies found clinical signs to be less sensitive and there fore support the use of routine contrast studies. 35,36 Some of the common reasons quoted in support of rou tine Gastrografin swallows on POD 1 are documentation (especially for young surgeons), ability to detect strictures, and the consideration that many CT scanners are not bar iatric patient-rated.…”
Section: Discussionmentioning
confidence: 99%
“…Por otro lado, la sensibilidad del ECTDS de rutina en el primer día de postoperatorio para la detección de filtración en este estudio fue 0%, aun menor a lo publicado en la literatura (entre 22 y 75%) 2,3,10 . Esto sería concomitante con la presentación clínica, ya que dentro del primer día postoperatorio sólo se ha presentado 8% de las filtraciones, siendo más frecuentes la filtración intermedia (entre 5º y 9º día postoperatorio), y tardía (10º o más) abarcando 45% y 33% de las filtraciones respectivamente 12 .…”
Section: Discussionunclassified
“…En directa proporción con ello se ha experimentado un explosivo aumento de las cirugías bariátricas, con resultados que van más allá del solo objetivo de la reducción del peso corporal, como por ejemplo el control de la diabetes mellitus. Estos procedimientos quirúrgicos no están exentos de complicaciones, siendo la más temida la filtración postoperatoria 2 , por lo que el diagnóstico oportuno de ella es necesario para disminuir la morbimortalidad en estos pacientes 3 .…”
unclassified
“…After reading the interesting article ''Predictive value of upper gastrointestinal studies versus clinical signs for gastrointestinal leaks after laparoscopic gastric bypass'' by Madan [1] et al, we want to contribute our opinion about the use of routine imaging tests (RIT) after laparoscopic Roux-en-Y gastric bypass (LRYGB). The efficiency of upper gastrointestinal (UGI) studies relies mainly on radiologist experience; besides, it is well known that computed tomography (CT) scanning has a better sensitivity and specificity [2] than UGI studies for detection of leaks.…”
mentioning
confidence: 99%